2023
DOI: 10.1038/s41467-023-41436-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a common ice nucleus on hydrophilic and hydrophobic close-packed metal surfaces

Pengcheng Chen,
Qiuhao Xu,
Zijing Ding
et al.

Abstract: Establishing a general model of heterogeneous ice nucleation has long been challenging because of the surface water structures found on different substrates. Identifying common water clusters, regardless of the underlying substrate, is one of the key steps toward solving this problem. Here, we demonstrate the presence of a common water cluster found on both hydrophilic Pt(111) and hydrophobic Cu(111) surfaces using scanning tunneling microscopy and non-contact atomic force microscopy. Water molecules self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…To the best of our knowledge, only cluster B was previously reported in literature, as part of the development of electrostatic discovery in AFM. 13 In light of a recent work 23 that showed the presence of a common 15-mer cluster on Cu(111) and Pt(111), we also observe that experiment A resembles the initial state of the 15-mer formation, potentially signaling its presence on Au(111) as well.…”
Section: Discussionsupporting
confidence: 71%
“…To the best of our knowledge, only cluster B was previously reported in literature, as part of the development of electrostatic discovery in AFM. 13 In light of a recent work 23 that showed the presence of a common 15-mer cluster on Cu(111) and Pt(111), we also observe that experiment A resembles the initial state of the 15-mer formation, potentially signaling its presence on Au(111) as well.…”
Section: Discussionsupporting
confidence: 71%
“…These thermal effects are attenuated at cryogenic temperatures as used in low-temperature scanning tunneling microscopy (LT-STM). This method opened new insights into the nucleation and growth of water structures on metal 21,35 or oxide surfaces 36,37 with 21,[35][36][37] or without [23][24][25][26][28][29][30][38][39][40][41][42][43] co-adsorbates at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of ice on different pristine metal surfaces have been largely investigated including the here-used Cu(111) surface, 24,33,39,43,44 and the other coinage metals, Ag(111), 23,32 and Au(111) 31,40,41 by direct imaging. In contrast, very little is known about the interaction of ions with water on surfaces so far.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption and reaction of methanol and water on copper surfaces have been investigated individually by many researchers over the past few decades using surface analysis techniques and theoretical calculation methods, in which scanning tunneling microscopy (STM) and atomic force microscopy (AFM) in combination with density functional theory (DFT) are ideal tools in identifying the H-bonding structures at the atomic scale. Low-temperature STM studies revealed that methanol forms zigzag chains and isolated hexamers on Cu(111) depending on the coverage and surface temperature . Besides, water creates various H-bonding networks on Cu(111) surfaces, including individual hexamers and nanoclusters at low temperatures and crystalline ice when annealing at 130 K. , Recent STM and AFM observed that water adsorbed on Cu(110) surface can form small clusters, which are mainly built from cyclic tetramers and pentamers at 20 K . Increasing surface temperature, water would aggregate into 1D pentagonal chains and hexagonal water–hydroxyl islands on Cu(110). , In contrast, the H-bonding structure and dynamics of alcohol–water mixtures on solid surfaces have just gotten attention in recent years. , Using in situ AFM and multiscale molecular simulations, it is revealed that mixed solutions of water and alcohols (methanol and ethanol) can be linked by hydrogen bonds to form a solid-like two-dimensional interfacial structure on graphite .…”
Section: Introductionmentioning
confidence: 99%